2018
DOI: 10.1111/iju.13706
|View full text |Cite
|
Sign up to set email alerts
|

Psychotherapy combined with drug therapy in patients with category III chronic prostatitis/chronic pelvic pain syndrome: A randomized controlled trial

Abstract: Psychological intervention therapy can effectively improve the psychological status and sexual function in patients with category III chronic prostatitis/chronic pelvic pain syndrome than the routine medication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 29 publications
(53 reference statements)
0
6
0
3
Order By: Relevance
“…This abnormal psychology such as depression, anxiety, hostility, and compulsion will eventually make patients lose confidence in treatment. The symptoms of type III prostatitis are mainly located in the lower abdomen, perineum, and other parts [ 18 ]. It is very easy for patients to associate symptoms with sexual function, which further increases the psychological burden of patients and induces psychological problems [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…This abnormal psychology such as depression, anxiety, hostility, and compulsion will eventually make patients lose confidence in treatment. The symptoms of type III prostatitis are mainly located in the lower abdomen, perineum, and other parts [ 18 ]. It is very easy for patients to associate symptoms with sexual function, which further increases the psychological burden of patients and induces psychological problems [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In their report, Wang et al . noted that CP/CPPS patients are more likely to have psychiatric symptoms than the general population, and assessment of severity with evaluation scales, such as the Self‐Rating Anxiety Scale and Self‐Rating Depression Scale, is important . However, it remains controversial whether the psychological intervention described in the present study is necessary for all patients with CP/CPPS symptoms.…”
mentioning
confidence: 89%
“…A recent review carried out in Europe showed the importance of a multimodal therapeutic approach for CP treatment; however, few studies of CP/CPPS have been carried out in Japan. Therefore, the present research results might be considered as reference findings for Japanese patients, as the study was carried out in Asia …”
mentioning
confidence: 91%
“…Choroba obejmuje elementy fizyczne, emocjonalne i psychologiczne. Skuteczne leczenie musi zatem skupiać się nie tylko na fizycznej patologii, ale także na emocjonalnych i psychologicznych aspektach zaburzenia [9]. Stosuje się wiele różnych terapii, w tym leki przeciwzapalne, antybiotyki, alfa-blokery, modulatory bólu neuropatycznego, inhibitory 5α-reduktazy, psychoterapię [6] i fizjoterapię dna miednicy [10] .…”
Section: Wprowadzenieunclassified